2012
DOI: 10.1089/dia.2011.0278
|View full text |Cite
|
Sign up to set email alerts
|

Vildagliptin Added to Metformin on β-Cell Function After a Euglycemic Hyperinsulinemic and Hyperglycemic Clamp in Type 2 Diabetes Patients

Abstract: The addition of vildagliptin to metformin gave a better improvement of glycemic control, insulin resistance, and β-cell function compared with metformin alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…However, eight trials reported co-primary outcomes to HbA 1c change from baseline [54, 59, 62, 64, 82–85], such as change from baseline in FPG, 2-hour postprandial glucose, BMI, body weight, fasting lipids, fasting plasma insulin, fasting insulin, fasting C-peptide, vital signs, and number/proportion of patients with adverse events, homeostatic model assessment-insulin resistance (β-cell function), and proportion of patients achieving HbA 1c <7%. In five trials, HbA 1c change from baseline was not the primary outcome [36, 53, 68, 86, 87].…”
Section: Resultsmentioning
confidence: 99%
“…However, eight trials reported co-primary outcomes to HbA 1c change from baseline [54, 59, 62, 64, 82–85], such as change from baseline in FPG, 2-hour postprandial glucose, BMI, body weight, fasting lipids, fasting plasma insulin, fasting insulin, fasting C-peptide, vital signs, and number/proportion of patients with adverse events, homeostatic model assessment-insulin resistance (β-cell function), and proportion of patients achieving HbA 1c <7%. In five trials, HbA 1c change from baseline was not the primary outcome [36, 53, 68, 86, 87].…”
Section: Resultsmentioning
confidence: 99%
“…We have already conducted several studies on incretins, two studies on exenatide [14,15], three studies on DPP-4 inhibitors sitagliptin and vildagliptin [16][17][18], a review about saxagliptin effects in combination with metformin [19], and a review about DPP-4 inhibitors [20] proving that, once metformin fails to maintain glycemic control, DPP-4 inhibitors addition could be a valid option to lower HbA 1c levels and to improve β-cell function without increasing body weight, also preventing the risk of hypoglycemia posed by sulfonylureas. Given the increasing use of incretins and the recent release of a new formulation of exenatide to be administered once weekly, this time we decided to conduct a review analyzing the clinical efficacy and safety of GLP-1 receptor agonists exenatide and liraglutide, both alone and in combination with other anti-diabetic drugs, including the most important studies involving them in the latest ten years.…”
Section: Incretins Physiological Aspectsmentioning
confidence: 99%
“…The arginine stimulation test (AST) has been used in islet autotransplantation studies in which the insulin secretory response to arginine correlates with the number of transplanted islets in this patient population (17,18). Although these various tests have been used to detect and quantify phenotypic differences across health and disease, their application to evaluate pharmacologic interventions has been demonstrated in a limited number of studies (1921). In particular, there is scant information on their variability and reproducibility characteristics.…”
Section: Introductionmentioning
confidence: 99%